2014
DOI: 10.1111/apa.12556
|View full text |Cite
|
Sign up to set email alerts
|

Children with juvenile idiopathic arthritis frequently experience interruptions to their medical therapy

Abstract: Our study shows a high percentage of interrupted medical therapies, due to adverse events or inefficacy, in children with JIA. Adverse events from methotrexate and biological agents were seldom severe. The results highlight the need for better predictive factors to guide therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…TNF-alpha inhibitors are used in approximately 20-25% of children with JIA in Sweden [29]. A review concluded that some children with JIA develop TMJ arthritis despite TNF-alpha inhibitors [4].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-alpha inhibitors are used in approximately 20-25% of children with JIA in Sweden [29]. A review concluded that some children with JIA develop TMJ arthritis despite TNF-alpha inhibitors [4].…”
Section: Discussionmentioning
confidence: 99%